The Role of Emotional Intelligence in Improving Student Self-Efficacy - Galuh Mentari Putri; Sekar Purbarini Kawuryan; Bambang Saptono; Zeva Adi Fianto (Jurnal Ilmiah Sekolah Dasar, 2024)
This study analyzes the influence of emotional intelligence on students' self-efficacy in an educational context. This research highlights the importance of good emotion management to maximize emotional intelligence, which impacts the ability to follow lessons and self-management in educational settings, especially in facing academic demands and life in the 21st century. This quantitative study involved 52 respondents who filled out a Google Form questionnaire. The instrument used consisted of 40 items measuring emotional intelligence and self-efficacy scales. The prerequisite tests included normality, linearity, and multicollinearity tests, while data analysis techniques employed regression with Pearson product-moment correlation approach. The results showed that emotional intelligence significantly affects students' self-efficacy, with a regression coefficient of 0.740 and a determination coefficient of 0.538. The significance of 0.000 (<0.05) indicates that emotional intelligence influences self-efficacy by 53.80%, while the remaining 46.20% is influenced by other variables not examined. This study concludes that emotional intelligence is important in enhancing students' self-efficacy, making it essential to develop it within the educational context. The implications of these findings emphasize the need for educational strategies that can enhance emotional intelligence to support academic success and students' personal development.